The Association Between Mother’s Care Practices With Stunting Incident In Children Age 12-35 Months In Air Dingin Primary Health Center Padang 2018 - Wahyu Zikria; Masrul Masrul; Lusiana El Sinta Bustami (Universitas Andalas, 2018)
Stunting is the long-term outcome of nutritionaldeficiency with height by age less than -2SD below themedian length who affects to decreased cognitive andphysical abilities in children. The aims of this study is todetermine the association between mother’s care practiceswith stunting incidennt in the children age 12-35 months inAir Dingin Primary Health Center Padang 2018. This study was a quantitative study with crosssectional design conducted at Air Dingin health center fromApril 2018 to May 2018. There were 77 mothers with 12-35month childrens became sample of this study. The motheras the respondent was interviewed directly with aquestionnaire. While the stunting incident was measured bybody height/age and interpreted by WHO-antro software.Data will analyzed in univariate and bivariate by using chisquareanalysis(p<0,05).The result of the study showed that 46,8% childrenssuffered stunting. The result of chi-square analysis revealedp-value between care practice for feeding (p=0,000), carepractice for hygiene (p=0,000), care practice for health(p=0,000) and care practice for psychosocial stimulation(p=0,000). There is an association between care practice forfeeding, care practice for hygiene, care practice for healthand care practice for psychosocial stimulation with stuntingincident. It is expected that mothers to pay more attention tocare practices provided to children so as to prevent theoccurrence of stunting in children.